"Steinstrasse" in the Biliary Tract. - Guzmán-Calderón, Edson (2017)
The presence of a stone or stones within the common bile duct (CBD) is known as choledocholithiasis. Choledocholithiasis is reported in 3%-22% of patients undergoing cholecystectomies [1]. A confirmatory diagnosis of choledocholithiasis is made using advanced imaging, including magnetic resonance cholangiopancreatography and endoscopic retrograde cholangiopancreatography (ERCP). Treatment varies locally; however, ERCP with sphincterotomy is most commonly employed with a high degree of success. Difficult anatomy and difficult stone burden require advanced surgical, endoscopic, and percutaneous techniques to extract or expel biliary stones.